2015
DOI: 10.1111/1750-3841.12854
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shape and Size of Agar Gels on Heating Uniformity During Pulsed Microwave Treatment

Abstract: Model gel systems with different shape (sphere, cylinder, and slab) and size (180 and 290 g) were prepared with agar (5%) and sucrose (5%). Dielectric constant (ε'), loss factor (ε"), thermophysical properties, and temperature distribution of the model system were measured. Each agar model system was immersed and suspended in water, and then, heated in a microwave oven with intermittent heating until the core temperature reached 50 °C. The ε' and ε" of agar gels decreased when frequency increased. The density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…To simulate the flesh, agar concentrations of 5, 10 and 15% were used with each artificial skin. Previous studies have shown that these agar concentrations have similar thermal behavior to those of fruit flesh (De Castro et al, 2004Soto-Reyes et al, 2015;Defraeye et al, 2017). However, studies attempting to simulate mango flesh have never been accomplished before.…”
Section: Artificial Fleshmentioning
confidence: 97%
See 2 more Smart Citations
“…To simulate the flesh, agar concentrations of 5, 10 and 15% were used with each artificial skin. Previous studies have shown that these agar concentrations have similar thermal behavior to those of fruit flesh (De Castro et al, 2004Soto-Reyes et al, 2015;Defraeye et al, 2017). However, studies attempting to simulate mango flesh have never been accomplished before.…”
Section: Artificial Fleshmentioning
confidence: 97%
“…This information can be used to develop artificial fruit with thermal behavior similar to real fruit. These studies have shown that agar concentrations from 1 to 5%, saccharose up to 5%, CaCl 2 of 0.2%, citric acid from 0 to 10% and pH from 0 to 4 affect the thermal behavior of the artificial flesh (De Castro et al, 2004;Birla et al, 2008;Soto-Reyes et al, 2015). Other simulations have been accomplished using a 3% agar solution for the flesh and polychlorinated vinyl (PVC) for skin of orange fruit.…”
Section: Thermal Simulations Of Fruit With Synthetic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…problems when dealing with materials that have a low flashing point or in high temperature conditions [16,17]. For studies on microwave heating uniformity improvement, the common methods could be categorized into two aspects [18]: (1) To improve the uniformity of the electromagnetic field in the microwave cavity, such as optimization of microwave power feeding situations [19][20][21][22], introducing of mode stirrers [23,24], application of conductive matter [25,26] and optimization of heating chamber structure [27,28]; (2) to improve the uniformity of microwave energy absorption, such as introducing of a rotating turntable or conveyor belt [29,30], optimization of the shapes and sizes of processing materials [26,31,32]. For studies on the electric discharge phenomena, related research has focused on microwave discharges in sintering of powdered metals.…”
Section: Geometrymentioning
confidence: 99%
“…The major challenges for commercial RF applications are non-uniform and run-away heating, such as overheating in corners and edges [20][21][22][23] . Many methods for improving the RF heating uniformity have been studied, such as hot air surface heating, conveyor movement, sample mixing [11,[24][25][26] , changing the shape of foodstuff [27,28] and using special material containers whose dielectric properties being similar to those of samples [29] . Among these methods, mixing is a very effective way to improve sample temperature distribution volumetrically [25] since the conveyor belt provides the limited RF heating uniformity improvement only along movement direction [30,31] .…”
Section: Introductionmentioning
confidence: 99%